ANALYSIS OF OLC SYSTEMS IN THE PERSPECTIVES OF RELEVANT COST AND CARBON EMISSION COST - Temy Setiawan; Ahalik; Vivian Whynne (UPT Publikasi Ilmiah UNISBA, 2023)
This research raises the topic of online learning and aims to identify and analyze online learning in terms of relevant costs. Online learning is a learning method that utilizes the internet and connected media to connect and learn. This research is qualitative with a case study method. The tools used in this research are Microsoft Excel and the GoGreener application to recapitulate and manage research sample data. The results of this study state that online learning in the midst of the COVID-19 pandemic situation is a great learning method. It is because by applying the online learning method, the costs incurred can be reduced (relevant) compared to the costs incurred during face-to-face or onsite learning, and the carbon costs that need to be paid can also be reduced. Keywords: Online Learning, Relevant Costs, Carbon Costs, COVID-19 Pandemic